Tests of a small compressed air plant - Correll, James A. (My University, 1903)
Introduction: The following tests were made on the compressed air plant in the Engineering Laboratory of the Kansas State Agricultural College. The plant is equipped as follows: a vertical engine the make and rated horse power of which are unknown, belted, through a main shaft, to a double acting, horizontal, piston compressor manufactured by the Ingersoll-Sergeant Drill company, and rated at from 8 to13 horse power depending on the revolution, piston compressor manufactured by the Ingersoll-Sergeant Drill Company, and rated at from 8 to 13 horse power depending on the revolutions per minute and the receiver pressure. A Westinghouse engine with two 6 x 8 single acting cylinders was connected to the air receiver and used as an air motor. The object of the tests was to determine 1st the efficiency of the plant, or the ratio of the developed brake horse power of the motor to the indicated horse power of the engine; 2nd the efficiency between the engine and compressor cylinders, and between the compressor cylinder and the brake on the motor; 2rd the horse power lost in heating the air and the cooling water. A series of three tests was conducted, the duration of each of which was one hour. Indicator cards were taken on the engine and compressor every five minutes throughout the test; as there was no means of taking cards on the air motor, a rope brake was constructed and used instead. Every five minutes, at the same time that the indicator cards instead. Every five minutes, at the same time that the indicator cards were taken, the speeds of the engine compressor and motor were noted, and at the same time, the initial and final temperatures of the air and cooling water, and the readings of the scale of the rope brake on the motor were taken. All water which passed through the water jacket of the compressor was carefully weighed and recorder, so that the total weight of water which passed through the jacket during the test was known.
Citation: Correll, James A. Tests of a small compressed air plant. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Efficiency of the Plant; Indicator Cards; Effective Pressure; Theses